Respon Antera Lilium longiflorum Thunb. dengan Berbagai Stadium Perkembangan Mikrospora pada Kombinasi Konsentrasi Zat Pengatur Tumbuh - Anggraeni, Anggraeni; Iriawati, Iriawati (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2017)
The right stage of microspore development to be used as explants become the critical factor for the successful of anther culture. Anther containing microspores at the pollen mother cell to binucleate stages were cultured on Murashige and Skoog (MS) media supplemented with various plant growth regulators. The media of 7.5 mM NAA + 0.75 mM BAP with bud size of 0.6-2.0 cm (pollen mother cell stage) are a combination that fits in callus, indirect shoot and direct shoot initiation with the percentage growth of each 30%; 16.6%; and 14.8%. Chromosome counts of root-tip cell of 89 regenerant revealed that 85 regenerant were diploids (95.5%) and 4 regenerant aneuploids (4.5%), but the haploid regenerants didn’t obtain. This result suggests that regenerants were derived from a somatic cells division.